Techno-totalitarianism? Challenges of new technologies for democracy - Quer, Santiago (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
In this paper we expose that the crisis that deliberative democracy is currently experiencing has as one of its possible outcomes the loss of democracy and the emergence of authoritarian regimes. And although this crisis does not necessarily have its origin in the evolution of information and communication technologies, we will show how they contribute to its expansion and deepening, and that, even more so, added these to certain characteristics that we observe in contemporary society, similar to those that Hannah Arendt identified in the societies in which the totalitarianisms of the twentieth century appear, generate the conditions of possibility for the emergence of a new type of totalitarianism, this time not based on terror, as were the totalitarianisms of the last century, but based on the capabilities that these technologies provide, which is why we have called it techno-totalitarianism, and that it would have the distinctive characteristics with respect to its predecessors that we will expose.
Keywords: totalitarianism; (Deliberative) Democracy; technology; social networks; surveillance